Rocuronium for intubation in parturients undergoing caesarean section - M., Sajina; Sangawar, Medha A.; A. V., Sangawar; Bannore, Niraj (International Journal of Research in Medical Sciences, 2018)
Background: Anaesthetic management of a parturient is a challenge because it involves simultaneous care of both mother and baby. Succinylcholine, a depolarizing muscle relaxant is most commonly used and considered “The Gold Standard’’ for tracheal intubation. Among currently available non-depolarizing neuromuscular blocking agent rocuronium bromide is the only agent that has rapid onset of action which is comparable to succinylcholine. Thus, rocuronium may provide alternative to succinylcholine for rapid sequence induction of anaesthesia wherever succinylcholine is contraindicated. Methods: In a control trial, 60 parturients of ASA grade I and II were randomly allocated in two groups of 30 patients each (group R and group S). After preoxygenation for a period of 5minutes rapid sequence induction done with thiopentone 5mg/kg for all patients. Muscle relaxant rocuronium (0.6mg/kg) was administered for group R. Succinylcholine was given in similar dosage (0.6mg/kg) for group S. The intubation was tried after 90 seconds in group R (rocuronium group) but after 60 seconds in group S (succinylcholie group). The intubating conditions were assessed and compared among the groups using criteria suggested by Cooper et al. Results: The mean intubation time was 98.3 seconds in group R and 67.9 seconds in group S. Rocuronium produced clinically acceptable intubating conditions in 28 out 30 patients (93.33%). Among these 28 patients 70% had excellent intubating conditions and 23.33% had good intubating conditions. Clinically acceptable intubating conditions were present in all 30 patients (100%-90% excellent and 10% good) who were administered succinylcholine. Succinylcholine produced excellent intubating conditions at 60 seconds (90 percent) compared to rocuronium (70 percent). However, this difference was statistically insignificant (p= 0.053). The mean Apgar score at 1 min and 5 min in group R was 8.1 and 8.83 as against 8.06 and 8.96 in babies born to mother in group S. Conclusions: Rocuronium (0.6mg/kg) provided acceptable intubation conditions after a waiting period of 90 seconds in 93.33% patients as against 100% patients in succinylcholine administered patients in equivalent dosage. So rocuronium is a promising alternative for rapid sequence induction in parturients in whom succinylcholine is not advisable or contraindicated.